REDUCING SUGAR CONTENT IN SIWALAN ROOMIE (Borassus flabellifer L) BEFORE COOKING AND LIQUID BROWN SUGAR AFTER COOKING - James Ngginak; Sonya Titin Nge; Filorita F. Klau; Coni Lisandra Balle Bisilissin (Universitas Medan Area, 2020)
Sugar reduction is one of the essential macronutrients used as energy sources. High levels of sugar reduction in food can increase the sweet taste of these foodstuffs. However, the consumption of high sugar food can cause diabetes mellitus. The purpose of this study is to increase the economic value of liquid palm sugar (Borassus flabellifer L) and opportunities as a preservative in the food industry. This research used quantitative descriptive methods. The results showed that the level of sugar reduction in siwalan liquid brown sugar (Borassus flabellifer L) was 15.65%, the water content in the liquid palm sugar sample (Borassus flabellifer L) is 26.78%, and the temperature of the liquid brown sugar after cooking is 230C. The effect of heat or temperature on cooking also causes physical changes in liquid brown sugar such as caramel formation, color and flavour.